Data base of Maximum heart rate prediction equations fail key external validation test - Portuguez Molina, Priscilla (2023)
Maximum heart rate (HRmax) equations have been used due to their simplicity and practicality, in comparison with stress tests. However, the best known “220-age” equation presents: low reliability and deviations of up to 12 beats/min. New formulas have been proposed, but these have not been correctly validated. The purpose of this study was to validate 7 prediction equations using an independent database. A database of 634 subjects (474 ​​men and 160 women) aged 18-85 years, obtained as part of a health service developed at the University of Michigan between 1990-1992, was used. Subjects performed a VO2max test on a treadmill, following a free protocol. The linear regression technique was used, in which the appropriate equations were those that met the 2 hypotheses: slope=1 and constant=0. According to the results, none of the equations analyzed for the entire sample accepted both hypotheses. When carrying out the analysis divided by sex, six of them met the two hypotheses for women, but none for men; and when performed divided by age group, 4 of the equations mee the hypotheses for the group of people with 40 years or younger, but not for the group of people over 40 years. HRmax. seems to be difficult to predict using a single equation, hence it is recommended that when a valid measure of this variable is needed, a stress test should be used.